3(s+5)=-2(3+9s)

Simple and best practice solution for 3(s+5)=-2(3+9s) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(s+5)=-2(3+9s) equation:



3(s+5)=-2(3+9s)
We move all terms to the left:
3(s+5)-(-2(3+9s))=0
We add all the numbers together, and all the variables
3(s+5)-(-2(9s+3))=0
We multiply parentheses
3s-(-2(9s+3))+15=0
We calculate terms in parentheses: -(-2(9s+3)), so:
-2(9s+3)
We multiply parentheses
-18s-6
Back to the equation:
-(-18s-6)
We get rid of parentheses
3s+18s+6+15=0
We add all the numbers together, and all the variables
21s+21=0
We move all terms containing s to the left, all other terms to the right
21s=-21
s=-21/21
s=-1

See similar equations:

| w+16=321 | | 50x+4=370 | | 7h−5h=14 | | 3x/4+11x/6=31/6 | | Y÷3+2x=70 | | N÷9-5n÷18=1÷9 | | 2(2x-3)=3x+10 | | 3k-2=46 | | 235.63+26.72=52.47d | | 2t=96 | | y−1/3y+7=10/1​ | | y−1/3y+7=10/1​ | | –3(4n–8)=–36 | | -8x-28=68 | | 8(8x-3)+2=-278 | | 29u=-406 | | -10=-4/n+7 | | 20+5y=9y | | -4x+(x)^2=0 | | y−1/3y+7=101​ | | 11/a=2.2 | | x={20±√(400–168)}/6 | | p-2.97=17.97 | | -3x-85=-7 | | 3x²–20x+14=0 | | 9.4=2x+1.2 | | 38=-2(3a-4)-7(4a-8)−38=−2(3a−4)−7(4a−8) | | 5(10y+2)=55 | | x^2-24x+60=0 | | 5(w-3)=3w-9 | | −4(2n+7)=20 | | 4+–2m=10 |

Equations solver categories